EFFECT OF WEIGHT CHANGE FOLLOWING INTENTIONAL WEIGHT LOSS ON BONE HEALTH IN OLDER ADULTS WITH OBESITY - Kammire, Daniel (Wake Forest University, 2019)
Objective: To examine change in bone mineral density (BMD) and trabecular bone score (TBS) one year after an 18 month weight loss intervention among weight regainers (WR) and weight loss maintainers (WM).
Keywords: Bone Health; Obesity; Older Adults; Trabecular Bone Score; Weight Loss; Weight Regain